Program parenting dalam meningkatkan kedisiplinan siswa ( studi kasus di MI Mambaul Hasan Batur Gading Probolinggo). - Mufidah, Nani Zahrotul; Aini, Nur (Universitas Islam Zainul Hasan Genggong, 2023)
This journal discusses the parenting program in improving student discipline (Case Study of MI Mambaul Hasan Batur Gading Probolinggo) The purpose of this research is to find out how the parenting program is implemented, the implementation of the parenting program and the factors that support and hinder the implementation of the parenting program. The results of the research that has been done regarding the parenting program in improving student discipline at MI Mambaul Hasan Batur Gading Probolinggo, namely the parenting program is intended for student guardians as a training tool to develop, hone, and provide new insights within the scope of how to educate children properly and correctly using the seminar method. The impact of the implementation of the parenting program held at MI Mambaul Hasan Batur Gading Probolinggo provides a good change in parents' parenting patterns towards their children, parents understand more about how to educate and discipline their children, so that children's discipline increases, both in discipline towards learning time and in discipline towards the rules in school. There are several factors that support and hinder the implementation of the parenting program held at MI Mambaul Hasan Batur Gading Probolinggo, including the existence of a good relationship between the school and student guardians, resource persons who are competent in parenting material and become good motivators for student guardians, the material delivered in accordance with the needs of student guardians. While the inhibiting factors include less than optimal preparation so that the socialization of the parenting program is not optimal.